Eﬀect of orthodontic adhesives modiﬁed with antibacterial nanoparticles on bond strength: literature review - H. Almokaddam; N. S. Tuturov; I. Katbeh; A. Saleh; I. Ibrahim (Эндодонтия Today)
RELEVANCE. With the advent of nanotechnology, new dental products are being created with the addition of various nanoparticles to improve the quality of the material, as well as increase their durability and antibacterial therapy. Recently, nanoparticles of silver, calcium hydroxyapatite, calcium dioxide, magnesium, cinnamon and vanillin are included in orthodontic adhesives to prevent enamel demineralization during ﬁxed appliance treatment. However, the strength of ﬁxation of the bracket system to the tooth enamel plays an important role in resisting orthodontic and mechanical stress in the oral cavity to achieve precise control of tooth movement.AIM. The purpose of this study is to provide an analytical review of laboratory studies on the shear bond strength of orthodontic adhesives modiﬁed with antibacterial nanoparticles.MATERIALS AND METHODS. The eLibrary, PubMed and Google Scholar databases were queried for scientiﬁc articles published from 2019 to 2024 using the keywords: nanoparticles, orthodontics, bond strength, orthodontic adhesive, nanoadhesive. Thus, this article included 13 in vitro studies on the topic of shear adhesion strength of nanoadhesives, the remaining 40 scientiﬁc articles were devoted to the study of methods of using nanotechnologies in the orthodontic clinic, the properties of various nanoparticles and the problems of demineralization of dental tissue during the correction of dentoalveolar anomalies, their prevention.CONCLUSION. Based on this analysis, it was found that most laboratory studies of orthodontic adhesives containing low concentrations of nanoparticles demonstrated positive antimicrobial potential while maintaining acceptable adhesive bond strength. However, further studies are needed in clinical settings, taking into account humidity and temperature changes in the oral cavity, to achieve the best mechanical performance and antibacterial eﬀectiveness against bioﬁlm-forming pathogens during orthodontic therapy.